2022
DOI: 10.1007/s12571-021-01253-w
|View full text |Cite
|
Sign up to set email alerts
|

Rice yield response to climate and price policy in high-latitude regions of China

Abstract: Climate change has renewed interest in the production capacity of agriculture. Few researchers paid attention to price policy and heteroscedasticity in yield model. We incorporate rice price policy into the yield model at the expected price using a Tobit procedure and take Kalman filter theory to explore useful information, and then estimate the rice yield response to climate and rice price using a spatial autoregressive combined model in high-latitude regions of China from 1992 to 2018. Meanwhile, we apply tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The uncertainty of output in the agricultural product supply chain is a risk that is difficult to grasp in agricultural production decision making. Natural disasters such as climate change will lead to a reduction in agricultural production, which is the main factor affecting the agricultural product market [13][14][15]. Assouto et al also confirmed that weather-induced uncertainty in agricultural output increases market price volatility [16].…”
Section: Literature Review 21 Agricultural Product Supply Chainmentioning
confidence: 99%
“…The uncertainty of output in the agricultural product supply chain is a risk that is difficult to grasp in agricultural production decision making. Natural disasters such as climate change will lead to a reduction in agricultural production, which is the main factor affecting the agricultural product market [13][14][15]. Assouto et al also confirmed that weather-induced uncertainty in agricultural output increases market price volatility [16].…”
Section: Literature Review 21 Agricultural Product Supply Chainmentioning
confidence: 99%
“…Such a threshold was not reached till AI reached 0.5, after which the yield will decline, in the case of LBIP. Yu et al (2022) also describes the increase in yield with increase in growing degree days (GDD) until a threshold GDD is reached, after which the yield decreases. An increase in rice yield with increase in temperature, as projected by the RCM RegCM3 was also reported in Cauvery river basin, of which Bhavani river basin is a part of (Geethalakshmi et al, 2011).…”
Section: Response To Climate Stressorsmentioning
confidence: 99%
“…Some research studying the effectiveness of the Chinese grain support policies focused on agricultural subsidy programs (e.g., Yi et al, 2015;Su et al, 2021;Fan et al, 2023). More recent studies focused on assessing the impacts of the price support policy in China on price enhancement and price stabilization (Li et al, 2022;Lyu & Li, 2019) and on price variability and welfare (Wang & Wei, 2021), as well as how rice yield responses to climate and rice price policy in China (Yu et al, 2022). As far as we are aware, there is not much research on evaluating the effectiveness of the minimum procurement price policy on the acreage change, which also considers the effect of rice price increases in the same period, except for Su et al (2021).…”
Section: Introductionmentioning
confidence: 99%